MEANING OBSCURITIES IN LECTURER-STUDENT COMMUNICATION - KABWE KANTANDA, MUPEMBA (IJRDO- Journal of Educational Research, 2021)
Abstract Effective teaching and learning depend on meaningful communication between the lecturer and the students. Unfortunately, while lecturing some meaning obscurities occur in the utterances. This fact is really a serious problem which necessitates a deep study so as to make the communication between lecturers and students more effective. This problem leads to this research question: “why are there meaning obscurities in Lecturer-Student Communication?”. To answer this research question, it is necessary to examine the utterances that occur in the Lecturer-Student Communication. Therefore, the aim of this article is to examine utterances occurring in the Lecturer-Student Communication so as to point out the meaning obscurities and their causes in Lecturer-Student Communication. To achieve this aim, 200 utterances were collected during the classroom observations in order to examine them on the basis of the lexical, compositional, utterance, and content analyses. This is to say, each of 200 utterances was analyzed at the level of lexical, compositional, and utterance so as to discover the meaning obscurities and their causes. After the analyses, the content analysis was used to classify the utterances with respect to Searle’s classification. The results revealed that the meaning obscurities occurring in the utterances are caused by misleading, vague, ambiguous, and obscure expressions. The discussion explains all these expressions so as to answer the research question related to the problem before the suggestions of effective strategies are given to avoid meaning obscurities in Lecturer-Student Communication. Key words: meaning obscurities, lecturer-Student Communication, utterances, misleading, vague, ambiguous, and obscure